Design-eligibility study of solar thermal helically coiled heat exchanging system with annular dimples by irreversibility concept. (January 2022) - Cao, Yan; Hashemian, Mehran; Ayed, Hamdi; Shawabkeh, Ali; Issakhov, Alibek; Wae-hayee, Makatar
Abstract: This is a numerical research that aims to design several helically grooved coils for solar water heating systems and compare them based on the irreversibility concept. To this end, helical coils with circle, square, horizontal elongated circle (HEC), and vertical elongated circle (VEC) cross-sections were annularly grooved for enhancing heat transfer rate. The Second law analysis in this study was performed based on several variables including flow rate (1–6 lit/min), geometrical, temperature (283–323K), and type of working fluid. Depth and distance of grooves were considered as geometrical parameters. Water, EG (CH2 OH)2 (IUPAC name: ethane-1, 2-diol), and Theminol-55 were used as heat transfer fluids. Selected fluids make a Pr range of 3.35–744. Various entropy-based indicators were used to select the most optimum condition. Moreover, the interactions between triple thermodynamic domains (energy, entropy, and exergy) were conceptualized. Results demonstrated that for all cases the highest entropy generation can be achieved in the higher flow rates (6 lit/min), also when groove depth and distance are, respectively, 1.3 mm and 20 mm. Case ''VEC'' has the lowest ratio of grooved dimensionless entropy to un-grooved dimensionless entropy. Graphical abstract: Image 1